High cell surface expression and peptide binding affinity of HLA-DQA1*05:03, a susceptible allele of neuromyelitis optica spectrum disorders (NMOSD) - Shohei Beppu; Makoto Kinoshita; Jan Wilamowski; Tadahiro Suenaga; Yoshiaki Yasumizu; Kotaro Ogawa; Teruyuki Ishikura; Satoru Tada; Toru Koda; Hisashi Murata; Naoyuki Shiraishi; Yasuko Sugiyama; et al. (Scientific Reports, 2022)
Abstract Neuromyelitis optica spectrum disorder (NMOSD) is a relapsing autoimmune disease characterized by the presence of pathogenic autoantibodies, anti-aquaporin 4 (AQP4) antibodies. Recently, HLA-DQA1*05:03 was shown to be significantly associated with NMOSD in a Japanese patient cohort. However, the specific mechanism by which HLA-DQA1*05:03 is associated with the development of NMOSD has yet to be elucidated. In the current study, we revealed that HLA-DQA1*05:03 exhibited significantly higher cell surface expression levels compared to other various DQA1 alleles, and that its expression strongly depended on the amino acid sequence of the α1 domain, with a preference for leucine at position 75. Moreover, in silico analysis indicated that the HLA-DQ encoded by HLA-DQA1*05:03 preferentially presents immunodominant AQP4 peptides, and that the peptide major histocompatibility complexes (pMHCs) are more energetically stable in the presence of HLA-DQA1*05:03 than other HLA-DQA1 alleles. In silico 3D structural models were also applied to investigate the validity of the energetic stability of pMHCs. Taken together, our findings indicate that HLA-DQA1*05:03 possesses a distinct property to play a pathogenic role in the development of NMOSD.